2018
DOI: 10.2174/1871520617666170919164055
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cell Necroptosis and Apoptosis Induced by Shikonin via Receptor Interacting Protein Kinases in Estrogen Receptor Positive Breast Cancer Cell Line, MCF-7

Abstract: On the basis of present findings, Shikonin has been suggested as a good candidate for the induction of cell death in ER+ breast cancer, although further investigations, experimental and clinical, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…As an anthraquinone compound derived from the roots of Lithospermum erythrorhizon , shikonin exhibits a broad spectrum of anti-tumor effects by inducing apoptosis in cancer of the gallbladder (18), pancreas (19), colon (20) and breast (21). The present study also demonstrated that shikonin inhibited glioma U251 cell proliferation in a dose- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…As an anthraquinone compound derived from the roots of Lithospermum erythrorhizon , shikonin exhibits a broad spectrum of anti-tumor effects by inducing apoptosis in cancer of the gallbladder (18), pancreas (19), colon (20) and breast (21). The present study also demonstrated that shikonin inhibited glioma U251 cell proliferation in a dose- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin is a naturally occurring naphthoquinone isolated from the root of the plant Lithospermum erythrorhizon, which has been widely used in the treatment of various disease [8]. In the recent years, studies have shown that shikonin and its derivatives have antitumor effects in wide range of cancer types including breast [9], lung [10], ovarian [11], liver [12], prostate [13], gastric [14] and pancreatic cancer [15]. However, the effects of shikonin in colorectal cancer cells have not been yet fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis is a form of regulated necrosis that depends on receptor-interacting protein kinase 1 (RIPK1) and can be specifically inhibited by necrostatin-1 (Nec-1) 6. Accumulating evidence has demonstrated that activated RIPK1 interacts with RIPK3 to facilitate RIPK1/RIPK3 necrosome formation 7,8. The necrosome recruits its downstream substrate, mixed lineage kinase domain-like protein (MLKL), which forms an oligomer, resulting in cellular membrane leakage and cell death 9.…”
Section: Introductionmentioning
confidence: 99%